Tight Adherence (Tad) Pilus Genes Indicate Putative Niche Differentiation in Phytoplankton Bloom Associated Rhodobacterales - Isaac, Ashley; Francis, Ben; Amann, Rudolf I.; Amin, Shady A. (Frontiers in Microbiology, 2021)
The multiple interactions of phytoplankton and bacterioplankton are central for our understanding of aquatic environments. A prominent example of those is the consistent association of diatoms with Alphaproteobacteria of the order Rhodobacterales. These photoheterotrophic bacteria have traditionally been described as generalists that scavenge dissolved organic matter. Many observations suggest that members of this clade are specialized in colonizing the microenvironment of diatom cells, known as the phycosphere. However, the molecular mechanisms that differentiate Rhodobacterales generalists and phycosphere colonizers are poorly understood. We investigated Rhodobacterales in the North Sea during the 2010–2012 spring blooms using a time series of 38 deeply sequenced metagenomes and 10 metaproteomes collected throughout these events. Rhodobacterales metagenome assembled genomes (MAGs) were recurrently abundant. They exhibited the highest gene enrichment and protein expression of small-molecule transporters, such as monosaccharides, thiamine and polyamine transporters, and anaplerotic pathways, such as ethylmalonyl and propanoyl-CoA metabolic pathways, all suggestive of a generalist lifestyle. Metaproteomes indicated that the species represented by these MAGs were the dominant suppliers of vitamin B12 during the blooms, concomitant with a significant enrichment of genes related to vitamin B12 biosynthesis suggestive of association with diatom phycospheres. A closer examination of putative generalists and colonizers showed that putative generalists had persistently higher relative abundance throughout the blooms and thus produced more than 80% of Rhodobacterales transport proteins, suggesting rapid growth. In contrast, putative phycosphere colonizers exhibited large fluctuation in relative abundance across the different blooms and correlated strongly with particular diatom species that were dominant during the blooms each year. The defining feature of putative phycosphere colonizers is the presence of the tight adherence (tad) gene cluster, which is responsible for the assembly of adhesive pili that presumably enable attachment to diatom hosts. In addition, putative phycosphere colonizers possessed higher prevalence of secondary metabolite biosynthetic gene clusters, particularly homoserine lactones, which can regulate bacterial attachment through quorum sensing. Altogether, these findings suggest that while many members of Rhodobacterales are competitive during diatom blooms, only a subset form close associations with diatoms by colonizing their phycospheres.